EXPERIENCES OF MOTHERS ACCOMPANYING HOSPITALIZED CHILDREN UNIT IN PEDIATRIC CLINIC - Luciano Marques dos Santos; Emanuelle Santos de Oliveira; Ana Celi Silva Torres Nascimento; Rosana Castelo Branco de Santana; Uliana Oliveira Catapano; Rívia e Silva Figueiredo; Valdimeires Santos Moreira (Revista Gestão & Saúde, 2014)
OBJECTIVE: To understand the experience of mothers accompanying hospitalized children in the Pediatric Clinic of a hospital in the interior of Bahia. METHODS: Descriptive, exploratory and qualitative study which complied with Resolution 196/96 and was developed in the Pediatric Unit, in the period between September and December 2009 through semi-structured interviews with eleven accompanying mothers. RESULTS:The illness and hospitalization occurr abruptly and generate the need for reorganization of family dynamics to meet the demands of the family members. As the accompanying mother will understand the dynamics of health workers, they stay calmer and try to understand the disease, care and her responsabilities. CONCLUSIONS: The accompanying mother needs to be recognized as a constant in the lives of sick children and within their family context, so that their actions and reactions child during hospitalization.